The inhibitory impact of collaboration on the continued influence effect of misinformation - Chen, Gongxiang; Zhong, Yuxuan; Li, Sujie (Frontiers in Psychology, 2024)
The continued influence effect (CIE) of misinformation refers to the persistence of misinformation's impact on memory and inference even when individuals are aware of a retraction.This study examined whether collaborative processes affect the CIE and investigated the underlying mechanisms through three experiments. Experiment 1 explored the general impact of collaboration on the CIE. Experiment 2 further dissected collaboration into turn-taking and free collaboration conditions, assessing their effects on the CIE at various recall intervals. Building on these findings, Experiment 3 delved into the mechanisms driving the differential effects of turn-taking and free collaboration on misinformation correction. Results revealed that turn-taking collaboration consistently mitigates the CIE, while the effect of free collaboration on misinformation correction is moderated by recall time. This variation is attributed to differences in re-exposure, cross-cuing, and forgetting across collaboration types. The present study contributes empirical support to the Knowledge Revision Theory of the CIE.